Analisis Perbandingan Algoritma Jaringan Syaraf Tiruan pada Proses Identifikasi Gerak Bahu - Fauziah Fauziah; Aris Gunaryati; Septi Andryana; Ira Diana Sholihati (Jurnal SISKOM-KB (Sistem Komputer dan Kecerdasan Buatan), 2019)
The research related to the analysis of Range of Motion on human movements continues to evolve along with the development of image processing techniques related to human motion can be used to assess the motion done whether it is appropriate. The stage among others is to perform motion acquisition and then convert motion video into multiple image frames. The second phase performs the image processing process consisting of the development phase segmentation algorithm, consisting of background subtraction, grayscale, filtering, threshold, dilation, erosion to silhouette formation. Artificial Neural Network is a concept of learning used and implemented using computer programs and able to complete many calculation processes during the learning process and is system Information processors that have similar characteristics to the human neural network. Results of calculations made from neural network algorithms get an accuracy value of 92.67% using Back propagation of neural networks and 68.13% using; a radialbased neural network function to determine 3 motions are adduction, hyperextension, and extension. DOWNLOAD FILE : FULL TEXT